Religious liberty in America : the First Amendment in historical and contemporary perspective - Murray, Bruce T. (Book collections on Project MUSE., 2008)
From the Publisher: In recent years a series of highly publicized controversies has focused attention on what are arguably the sixteen most important words in the U.S. Constitution: "Congress shall make no law respecting an establishment of religion, or prohibiting the free exercise thereof." The ongoing court battles over the inclusion of the words "under God" in the Pledge of Allegiance, the now annual cultural quarrel over "Merry Christmas" vs. "Happy Holidays," and the political promotion of "faith-based initiatives" to address social problems-all reflect competing views of the meaning of the religious liberty clauses of the First Amendment. Such disputes, as Bruce T. Murray shows, are nothing new. For more than two hundred years Americans have disagreed about the proper role of religion in public life and where to draw the line between church and state. In this book, he reexamines these debates and distills the volumes of commentary and case law they have generated. He analyzes not only the changing contours of religious freedom but also the phenomenon of American civil religion, grounded in the notion that the nation's purpose is sanctified by a higher authority-an idea that can be traced back to the earliest New England colonists and remains deeply ingrained in the American psyche. Throughout the book, Murray connects past and present, tracing the historical roots of contemporary controversies. He considers why it is that a country founded on the separation of church and state remains singularly religious among nations, and concludes by showing how the Supreme Court's thinking about the religious liberty clauses has evolved since the late eighteenth century.